GOVERNMENT EXPENDITURES WITHOUT GROWTH: THE CASE OF TURKEY - SÖYLEMEZ, ARİF ORÇUN; ZÜLFÜOĞLU, ÖZKAN (MEHMET AKIF ERSOY UNIV, 2021)
Share of government expenditures in the GDPs are increasing virtually everywhere. Available data for developed countries indicate that the beginnings of this upward trend date back to the mid-19th century. Interestingly, economic growth rates did not increase significantly over time despite the increases in government expenditures. Low income countries today spend more than the double of what today's developed economies were spending on average in 1900. However, this is not helping them to converge to richer economies. Why are government expenditures increasing then? This question might have global pertinence but due to the variety of country-specific factors, it can be best studied on a single country level. In this article, the country of focal interest is Turkey. Five important variables that might affect government expenditures from different angles are evaluated regarding their contributions to the out-of-sample predictions of government expenditures using random forest methodology. Military expenditures are estimated as primarily important for determining the government expenditures in Turkey in the last fifty years, while tax collections happened to be the second most important factor affecting the ups and downs of government expenditures around a time-varying average line. Per capita income, urbanization and inflation also affect government expenditures in various ways.
Keywords: Government Expenditures; Machine Learning; Random Forests